3D conductive material strategies for modulating and monitoring cells. (March 2023) - Li, Xiao; Mao, Mao; Han, Kang; Yao, Cong; Gu, Bingsong; He, Jiankang; Li, Dichen
Abstract: Electrically conductive materials have been integrated into 3D bioengineered structures, such as tissue-engineered scaffolds, in vitro biological models, and therapeutic devices, to interface with cells and tissues for improving cell growth, differentiation, and functions. In recent years, remarkable efforts have been devoted to transforming conductive materials in 3D bioengineered structures into electronic components for stimulating cells and recording cellular signals. This emerging research frontier holds great promise to generate effective tools for understanding and manipulating biological systems, and its development calls for expertise across a broad range of research fields. In this article, we survey the state-of-the-art advances regarding 3D conductive bioengineered structures for modulating and monitoring cells in four critical aspects: basic conductive materials with distinctive characteristics can serve as building blocks; the design of conductive bioengineered structures can draw on the growing mechanistic understanding of structure–cell interplays; fabrication techniques have rapidly advanced to generate 3D bioengineered structures with complex electronic components for stimulating and sensing functionalities; furthermore, the applications of novel 3D conductive bioengineered structures have made a considerable impact on various biomedical fields. Finally, we discuss the future outlook and challenges for deeper integration and closer interactions between 3D conductive bioengineered structures and biological systems.